Two New Supramolecular Assemblies Obtained by Reaction Between Saccharin and Long-chain Diamines - Castellano, Eduardo Ernesto (2009)
The crystal structures of heptamethylenediammonium bis(saccharuinate) monohydrate,[H3N-(CH2)7-NH3](sac)2.H2O (I) and octamethylenediammonium bis(saccharinate) hemihydrate, [NH3-(CH2)8-NH3].1/2H2O (II) were determined by single-crystal X-ray diffraction methods. Compound I crystallizes in the triclinic space group P(-1) with 2 molecules per unit cell, and II in the monoclinic space group P21/a with Z = 4. The saccharinate moiety is planar in both compounds. The ionic crystals are further stabilized by an extensive H-bonding network, which links the anions and cations into an infinite three dimensional supramolecular assembly. The FTIR spectra of the adducts are briefly discussed in comparison with those of the constituent molecules.